Phylogeography and taxonomic revision of the New Zealand cryptic skink (Oligosoma inconspicuum; Reptilia: Scincidae) species complex - Chapple, David G.; Bell, Trent P.; Chapple, Stephanie N. J.; Miller, Kimberly A.; Daugherty, Charles H.; Patterson, Geoff B. (Zootaxa, 2011)
The New Zealand skink fauna is highly diverse and contains numerous cryptic, undescribed or hitherto undiscovered species. We completed a taxonomic revision of the cryptic skink (Oligosoma inconspicuum) species complex using molecular (550 bp of the ND2 mitochondrial gene) and morphological analyses. Four new species are described, with each diagnosable by a range of morphological characters and genetic differentiation from several closely related species: O. inconspicuum (sensu stricto), O. notosaurus, O. maccanni, O. stenotis and O. grande. Oligosoma tekakahu sp. nov. is restricted to Chalky Island in Fiordland, and is most closely related to O. inconspicuum and O. notosaurus. The other three new species are restricted to particular mountainous regions in central and western Otago (O. burganae sp. nov., Lammermoor and Rock and Pillar Ranges; O. toka sp. nov., Nevis Valley; O. repens sp. nov., Eyre Mountains) and are most closely related to O. stenotis and O. grande. We also re-described O. inconspicuum. Two proposed new taxa, the ‘Big Bay’ skink and ‘Mahogany’ skink, were found to represent Westland/Fiordland populations of O. inconspicuum rather than distinct taxa. We discuss the evolutionary and phylogeographic implications of cryptic and ‘anti-cryptic’ species within the O. inconspicuum species complex, and suggest that morphologically aberrant populations are the result of local adaptation to novel selective regimes.